Successful treatment of gamma 1 heavy chain deposition disease with bortezomib and dexamethasone - Masanori Sudo; Takuya Wakamatsu; Tomomi Ishikawa; Masato Habuka; Michihiro Hosojima; Suguru Yamamoto; Yumi Ito; Naofumi Imai; Yoshikatsu Kaneko; Akira Shimizu; Ichiei Narita (Human Pathology: Case Reports, 2019)
Heavy chain deposition disease (HCDD) is a rare complication of plasma cell dyscrasias, characterized by nonamyloid tissue deposits of incomplete monoclonal heavy chains in renal tissues. We report the case of a 78-year-old female with HCDD who was successfully treated with bortezomib and dexamethasone (BD); histopathological improvements were confirmed by kidney biopsy after 2 years of chemotherapy. She presented with renal insufficiency, proteinuria, hematuria, hypogammaglobulinemia, and hypocomplementemia. Renal biopsy showed diffuse global nodular glomerulopathy with the deposition of IgG1 and C3 in the glomeruli and on the tubular basement membrane. Kappa and lambda light chains were not detected. Staining for the constant regions of the gamma heavy chain revealed the absence of the CH1 domain. These findings are consistent with those of gamma 1 HCDD. Results of liquid chromatography-tandem mass spectrometric analysis were consistent with the immunohistochemical results. Two years after weekly BD therapy, normalization of the kappa/lambda ratio and reduction of urinary protein excretion were achieved. A follow-up biopsy showed remarkable diminution of nodular lesions of glomeruli and deposits of IgG and C3. Keywords: Heavy chain deposition disease, Bortezomib, Liquid chromatography-tandem mass spectrometry